Contemporary cultures of display - Barker, Emma. (New Haven : Yale University Press, 1999)
Part 1: The changing museum. The modern art museum / Christoph Grunenberg ; The museum in a postmodern era : the Musée d'Orsay / Emma Barker ; The Sainsbury Wing and beyond : the National Gallery today / Emma Barker and Anabel Thomas ##Part 2: Exhibition-ism. Exhibitions of contemporary art / Sandy Nairne ; Exhibiting the canon : the blockbuster show / Emma Barker ; Africa on display : exhibiting art by Africans / Elsbeth Court ##Part 3: Art in the wider culture. The museum in the community : the new Tates / Emma Barker ; Heritage and the country house / Emma Barker ; Contemporary art in Ireland, part one : institutions, viewers and artists / Nick Webb and Emma Barker ; Contemporary art in Ireland, part two : Alice Maher and Willie Doherty - location, identity and practice / Fionna Barber.
Adundo, Magdalene ; Andre, Carl ; Barber, Thomas ; Bermejo, Bartolomé ; Bouguereau, William Adolphe ; Bulloch, Angela ; Cabanel, Alexandre ; Camp, Sokari Douglas ; Christo & Jeanne-Claude ; Cormon, Fernand ; Courbet, Gustave ; Couture, Thomas ; Cranach, Lucas ; Cézanne, Paul ; David, Jacques-Louis ; Doherty, Willie ; Dürer, Albrecht ; Emokpae, Erhabor ; Francesca, Piero della ; Francesco, Piero della ; Friedrich, Caspar David ; Gaertner, Eduard ; Gormley, Antony ; Guercino ; Guerrilla Girls ; Haacke, Hans ; Hamilton, Richard ; Harvey, Marcus ; Hepworth, Barbara ; Hirst, Damien ; Holbein, Hans ; Hollein, Hans ; Johns, Jasper ; Jones, Thomas ; Kelly, Ellsworth ; Kemp, David ; Kosuth, Joseph ; Maher, Alice ; Malraux, André ; Manet, Edouard ; Mansueti, Giovanni ; Mhlaba, Dumile ; Michelangelo ; Mondriaan, Piet ; Monet, Claude ; Newman, Barnett ; Nicholson, Ben ; Nolde, Emil ; Oldenburg, Claes ; Parker, Cornelia ; Picasso, Pablo ; Pollock, Jackson ; Rubens, Pieter Paul ; Ruff, Thomas ; Samb, Issa ; Seurat, Georges ; Spoerri, Daniel ; Stubbs, George ; Takis ; Titian ; Tokoudagba, Cyprien ; Tunga ; Turner, J.M.W. ; Vinci, Leonardo da ; Warhol, Andy ; van Gogh, Vincent
CCS Gent
Includes bibliographical references and index.
boek